2016
DOI: 10.1186/s12985-016-0562-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 attenuates Japanese encephalitis virus replication by targeting DNM2

Abstract: BackgroundJapanese encephalitis virus (JEV) is a mosquito-borne flavivirus that causes acute viral encephalitis in humans. Pigs are important amplifier hosts of JEV. Emerging evidence indicates that host microRNAs (miRNAs) play key roles in modulating viral infection and pathogenesis. However, mechanistic studies delineating the roles of miRNAs in regulating host-JEV interactions remain scarce.ResultsIn this study, we demonstrated that miR-124 inhibited JEV replication in porcine kidney epithelial PK15 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…The RPPA study identified additional proteins that may be targeted by these miRNAs, such as miR-744 targeting of Akt or miR-124a and miR-24 suppression of GSK-3β, as both of these factors were previously shown to be important for influenza virus entry 56, 57. Other previously identified roles of these miRNAs in viral infection include miR-24 suppression of Kruppel-like factor 6, which is induced by RSV infection to induce cell-cycle arrest, 14 as well as the suppression of furin by miR-24, which is required for influenza virus activation, 58 and miR-124a attenuation of Japanese encephalitis virus (JEV) via targeting dynamin2, which is required for efficient JEV replication 59 . Therefore, it is highly probable that the broad-spectrum antiviral activity exhibited by these miRNA mimics is caused by their ability to downregulate multiple host factors that are essential for numerous DNA and RNA viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The RPPA study identified additional proteins that may be targeted by these miRNAs, such as miR-744 targeting of Akt or miR-124a and miR-24 suppression of GSK-3β, as both of these factors were previously shown to be important for influenza virus entry 56, 57. Other previously identified roles of these miRNAs in viral infection include miR-24 suppression of Kruppel-like factor 6, which is induced by RSV infection to induce cell-cycle arrest, 14 as well as the suppression of furin by miR-24, which is required for influenza virus activation, 58 and miR-124a attenuation of Japanese encephalitis virus (JEV) via targeting dynamin2, which is required for efficient JEV replication 59 . Therefore, it is highly probable that the broad-spectrum antiviral activity exhibited by these miRNA mimics is caused by their ability to downregulate multiple host factors that are essential for numerous DNA and RNA viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of reports have shown the dysregulation of microRNAs in various diseased conditions . We and others have reported the role of microRNA during JE neuroinflammation, where the virus impairs the function of microRNA and affect the down‐stream signaling in human brain microglial cells …”
Section: Discussionmentioning
confidence: 93%
“…Previously published reports by our and other's research group already demonstrated the role of microRNA in JEV infected microglial cells. 13,19,21…”
Section: Target Identification Of Significantly Perturbed Micrornasmentioning
confidence: 99%
See 2 more Smart Citations